DESIGN SISTEM PAKAN IKAN OTOMATIS UNTUK KOLAM IKAN NILA BERBASIS ARDUINO UNO - Sabni Gilang Permana; Muhammad Arifin, Abdul Nasar, Farell Muhammad Dava, Paduloh (ADISAM PUBLISHER, 2025)
For aquaculture to be successful, tilapia fish must be fed on schedule. To increase the efficacy and efficiency of feeding, this research attempts to design and create an automatic fish feeding system based on an Arduino Uno. Servo motors operate as actuators in this system, which uses a Real-Time Clock (RTC) to automatically set the feeding schedule and distribute feed to the pond at a predefined time. In order to create the feeding schedule twice a day, at 01.00 WIB and 17.00 WIB, this research entails creating hardware, including an Arduino Uno, LCD, and servo motor, as well as writing computer code. The outcomes of the deployment demonstrate that the system can function reliably and satisfy farmers' demands while preserving feeding accuracy. The potential of this system is